2022
DOI: 10.1111/jfpp.16655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of growing conditions on proximate, mineral, phenolic composition, amino acid profile, and antioxidant properties of black gram, mung bean, and chickpea microgreens

Abstract: In this study, proximate, minerals, chlorophyll, amino acids (AAs), phenolics, and antioxidant properties of black gram, mung bean, and chickpea microgreens grown under different conditions (soil, water, and coco‐peat with nutrient solution [CNS])were investigated. The yield, moisture, ash content (AC), and protein content of microgreens extract powder (MEP) varied from 7.31%–11.09%, 5.63%–8.96%, 9.31%–13.63%, and 51.07%–60.41%, respectively. The total chlorophyll content (TCC), flavonoid content (TFC), phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Among the families of microgreens studied, the Chenopodiaceae family ( bathua ) exhibited slightly higher protein content (3.40%) than Fabaceae (Bengal gram) (2.6%), Amaranthaceae (spinach) (2.56%), and Apiaceae (carrot) (2.43%). Additionally, our findings showed that the protein content in spinach was slightly higher than that reported in a previous study by Ghoora et al However, the protein content of Bengal gram microgreens is less in comparison to the investigation done by Kaur et al Carrot microgreens exhibited the highest dietary fiber content (2.4%) compared to the Amaranthaceae and Fabaceae families. Microgreens obtained from carrot exhibited the highest ash content; however, the maximum value observed did not exceed 1.36%.…”
Section: Resultsmentioning
confidence: 99%
“…Among the families of microgreens studied, the Chenopodiaceae family ( bathua ) exhibited slightly higher protein content (3.40%) than Fabaceae (Bengal gram) (2.6%), Amaranthaceae (spinach) (2.56%), and Apiaceae (carrot) (2.43%). Additionally, our findings showed that the protein content in spinach was slightly higher than that reported in a previous study by Ghoora et al However, the protein content of Bengal gram microgreens is less in comparison to the investigation done by Kaur et al Carrot microgreens exhibited the highest dietary fiber content (2.4%) compared to the Amaranthaceae and Fabaceae families. Microgreens obtained from carrot exhibited the highest ash content; however, the maximum value observed did not exceed 1.36%.…”
Section: Resultsmentioning
confidence: 99%
“…The agricultural and horticultural microgreen plant requires specific temperatures and humidity for production in closed and open systems. Temperature and humidity of 30–33 °C, 75–80% for rice grass, 15–32 °C, 80–85% for barley grass, 16–27 °C, 75–80% for oat grass, 23–28 °C, 60–70% for wheat grass, 29–32 °C, 30% for jowar grass, 25–34 °C, 52–88% for maize grass, 10–21 °C, 8–80% for buckwheat, 21–26 °C, 14–16% for chickpea, 18–21 °C, 50–60% for mint, 17–27 °C, 60–70% for coriander, 21 °C, 50–60% for basil, 24–29 °C, 75% for rosemary, 32 °C, 95–100% for parsley, 9.2–23.8 °C, 50–100% for saltwort, 21 °C, 50–70% for shisho, −1.11 °C, 50–75% for sorrel, 18–23 °C, 60–70% for sage, 18–23 °C, 40–60% for beet, 15–24 °C, 50–70% for chard, 24–26 °C, 11–96% for quinoa, 22–26 °C, 100% for spinach, 33–36 °C, 80% for chives, 32–50 °C, 65–75% for garlic, 18–23 °C, 95–100% for leek, 55–75 °C, 40–50% for onion, 15–21 °C, 60–70% for carrot, 14–26 °C, 90–95% for celery, 16–18 °C, 58–63% for dill, 60–70 °C, 50–65% for fennel, 10–29 °C, 50–60% for radish, 15–17 °C, 50–60% for aster cress, 15–21 °C, 76% for mustard, 7.2–29.4 °C, 55–65% for kale, 25–30 °C, 40–70% for kohlrabi, 7.2–18 °C, 90–95% for arugula, 25 °C day/23 °C night, 60% for sunflower, 25–34 °C, 50–60% for linseed, 23–25 °C, 90–95% for chicory, 15–18 °C, 95–98% for endive, 20 °C, 80% for lettuce, 15–21 °C, 40–50% for beans, 12–25 °C, 40–50% for welsh onion, 12–25 °C, 40–50% for long green onion, and 23–32 °C, 90–95% for red swiss chard are required for microgreen plant production.…”
Section: Factors Affecting In Microgreen Plant Production In Soilless...mentioning
confidence: 99%
“…95,96 The agricultural and horticultural microgreen plant requires specific temperatures and humidity for production in closed and open systems. Temperature and humidity of 30−33 °C, 75−80% for rice grass, 97 15−32 °C, 80−85% for barley grass, 98 16−27 °C, 75−80% for oat grass, 99 23−28 °C, 60−70% for wheat grass, 100 29−32 °C, 30% for jowar grass, 101 25−34 °C, 52−88% for maize grass, 102 10−21 °C, 8−80% for buckwheat, 103 21−26 °C, 14−16% for chickpea, 104 18−21 °C, 50−60% for mint, 105 17−27 °C, 60−70% for coriander, 106 21 °C, 50−60% for basil, 107 110 21 °C, 50−70% for shisho, 111 −1.11 °C, 50−75% for sorrel, 112 18−23 °C, 60−70% for sage, 113 18−23 °C, 40− 60% for beet, 114 15−24 °C, 50−70% for chard, 115 24−26 °C, 11−96% for quinoa, 116 22−26 °C, 100% for spinach, 117 33−36 °C, 80% for chives, 118 32−50 °C, 65−75% for garlic, 119 18−23 °C, 95−100% for leek, 120 55−75 °C, 40−50% for onion, 121 15−21 °C, 60−70% for carrot, 122 14−26 °C, 90−95% for celery, 123 16−18 °C, 58−63% for dill, 124 60−70 °C, 50−65% for fennel, 125 10−29 °C, 50−60% for radish, 126 15−17 °C, 50−60% for aster cress, 127 15−21 °C, 76% for mustard, 128 7.2−29.4 °C, 55−65% for kale, 129 25−30 °C, 40−70% for kohlrabi, 130 7.2−18 °C, 90−95% for arugula, 131 25 °C day/23 °C night, 60% for sunflower, 132 25−34 °C, 50−60% for linseed, 133 23−25 °C, 90−95% for chicory,…”
Section: Microgreen Plant Production In Soilless Culturementioning
confidence: 99%
“…They enhance the color, texture, and flavor of food products and improve health functions. Microgreens are a rich source of different vitamins (A, C, E, and K), , minerals (K, Ca, Fe, Zn, P, S, Mg, Mn, Cu, and Na) and health-promoting compounds such as phenolic compounds, amino acids, glucosinolates, and glycerophospholipids. ,, …”
Section: Introductionmentioning
confidence: 99%